Safety, Tolerability, and Pharmacokinetics of NK-104-NP: A Multicenter, Randomized, Placebo-Controlled Phase I Investigator-Initiated Trial for Intravenous Administration of Pitavastatin-Loaded PLGA Nanoparticles (NK-104-NP) in Healthy Japanese Male Subjects - Nakano, Kaku; Matoba, Tetsuya; Koga, Jun-ichiro; Kashihara, Yushi; Fukae, Masato; Ieiri, Ichiro; Shiramoto, Masanari; Irie, Shin; Kishimoto, Junji; Todaka, Koji; Egashira, Kensuke (International Heart Journal, 2018)
Pulmonary hypertension (PH) is a disease with poor prognosis, caused by the obstruction/stenosis of small pulmonary arteries. Statin is known to have vasodilating and anti-inflammatory property and is considered to be a candidate of therapeutic agents for the treatment of PH, but its efficacy has not been verified in clinical trials. We have formulated pitavastatin incorporating nanoparticles composed of poly (lactic-co-glycolic acid) (NK-104-NP) to improve drug delivery to the pulmonary arteries and evaluated their safety and pharmacokinetics in healthy volunteers. To accomplish this purpose, phase I clinical trials were conducted. In the single intravenous administration regimen, 40 healthy subjects were enrolled and PK (pharmacokinetic) parameters in 4 groups (1, 2, 4, and 8 mg as pitavastatin calcium) were as follows: 1.00 hour after the administration, the plasma concentration of pitavastatin reached Cmax (the maximum drug concentration) in all groups. Cmax, AUC0-t (area under the curve from time 0 to the last measurable concentration) and AUC0-∞ (area under the curve from time 0 extrapolated to infinite time) were increased in a dose-dependent manner. Population pharmacokinetic analysis based on these results indicated no accumulation of pitavastatin after repeated administration of NK-104-NP for 7 days. In this 7-day administration trial, the mean Cmax and AUC0-∞ of pitavastatin were not significantly different between days 1 and 7, suggesting that pitavastatin is unlikely to accumulate after repeated administration. In these trials, three adverse events (AEs) were reported, but they were resolved without any complications and judged to have no causal relationships with NK-104-NP. These results indicate that the innovative nanotechnology-based medicine NK-104-NP exhibited dose-dependent pharmacokinetics and was well tolerated with no significant AEs in healthy volunteers.